Pengaruh pH Terhadap BOD, TSS, Dan VFA Pada Pengolahan LindiDalam Bioreaktor Anaerobik - Abdul Kahar; Megahapsari Martaningtyas; Budi nining widiarti; ika Meicahayanti (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Leachate is a liquid waste resulted from physical, biological and chemical decomposition of landfill waste. Leachate contains complex dissolved organic and anorganic substrate which are biodegradable and nonbiodegradable.Anaerobictreatmentprincipallyutilizesanaerobicbacteriainordertodegradethedissolvedorganicsubstance. Anaerobic treatment is very sensitive towards the substrate cocentration and pH. The objective of this research is to decide the pH effect on the BOD, TSS and VFA at leachate treatment in anaerobic bioreactor. This research used anaerobic bioreactor with the volume of 160 L. Anaerobic treatment carried out for 21 days, at pH ambient, 7.2 and 8.0. Microorganisms used comes from cow rumen and leachate with a ratio of 1:3 and filtered to take the extract. Collecting data and BOD, TSS and VFA analysis were done every two days. The results showed that the pH effect to the decrease BOD, TSS, and VFA at leachate treatment in anaerobic bioreactor. Anaerobic bioreactor performance optimum at pH 7.2, with the reduction of BOD and TSS was 80.29% and 74.08% respectively,andthe range of VFA productionwas 91.15-185.25 mg/L.